2019
DOI: 10.1175/mwr-d-18-0412.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions for Nighttime Offshore Migration of Precipitation Area as Revealed by In Situ Observation off Sumatra Island

Abstract: The diurnal cycle over tropical coastal waters is characterized by offshore migration of precipitation area during nighttime. This study analyzes in situ observational data collected during the YMC-Sumatra 2017 field campaign around the western coast of Sumatra Island, Indonesia, to examine the offshore migration phenomenon during 5–31 December 2017, when the Research Vessel Mirai was deployed about 90 km off the coast to perform observation. The offshore migration is observed in only less than a half of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 51 publications
3
48
1
Order By: Relevance
“…Precipitation then redeveloped offshore at 0300 LT and persisted through the early morning. This nighttime/early morning precipitation maximum over the ocean has been widely observed and studied in the tropics (Kraus 1963;Ruppert et al 2013;Yang and Smith 2006), and is thought to be more pronounced during convectively active periods (Sakaeda et al 2018). During active BSISO phases, the diurnal cycle over land was once again very clear.…”
Section: ) Rainfallmentioning
confidence: 69%
See 3 more Smart Citations
“…Precipitation then redeveloped offshore at 0300 LT and persisted through the early morning. This nighttime/early morning precipitation maximum over the ocean has been widely observed and studied in the tropics (Kraus 1963;Ruppert et al 2013;Yang and Smith 2006), and is thought to be more pronounced during convectively active periods (Sakaeda et al 2018). During active BSISO phases, the diurnal cycle over land was once again very clear.…”
Section: ) Rainfallmentioning
confidence: 69%
“…These gravity waves lead to destabilization over the adjacent waters thereby supporting convection. This was also the mechanism offered by Yokoi et al (2017) to explain the offshore movement of convection observed near the island of Sumatra during the Years of the Maritime Continent (YMC) pilot field campaign. In this field project, a cooling (and subsequent destabilization) of potential temperature was noted in the lower free troposphere on days when offshore precipitation was greatest.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…(2) same functions of GWs but excited by the evaporative cooling of land precipitation (e.g., Hassim et al, 2016;Love et al, 2011;Vincent & Lane, 2016;Yokoi et al, 2017); (3) gravity (or density) currents, such as land breezes and cold outflows, which trigger new convection via convergence with ambient winds or cold outflows from other islands (e.g., Fujita et al, 2010;Houze et al, 1981;Mori et al, 2004;Wapler & Lane, 2012;Wu et al, 2009); and (4) influences of ambient winds, such as the advection effect (e.g., Ichikawa & Yasunari, 2006Yanase et al, 2017) and the vertical wind shear mechanism (e.g., LeMone et al, 1998;Yokoi et al, 2019). With these proposed mechanisms, we still do not know which one is the dominant process and how they vary with different islands in the MC.…”
Section: Introductionmentioning
confidence: 99%